Dynamic Modeling, and Simulation of Hybrid Solar Photovoltaic, and PEMFC Fuel Cell Power System - Sami, S.; Marin, E. (RA Journal of Applied Research, 2018)
The dynamic energy conversion equations have been developed to describe the behavior of a hybrid system of solar photovoltaic, and fuel cell as well as hydrogen storage. The system of equations has been integrated, and solved simultaneously using finite difference formulation. The dynamic model is intended for optimization and design purposes. On-site data was used to validate the simulation, program under various conditions. Comparison between the data and predicted results showed a fairagreement.